Influence of Service Quality and Price on Customer Satisfaction - Buchori Buchori; Andi Kurniawan; Hikmatul Aliyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the effect of service quality and price on customer satisfaction in Dalupa Trans travel services. In this study the population is consumers. Not all users of travel services are also passengers of Travel Dalupa Trans. The number of population in this study is not limited. The sample taken is 100 respondents by giving questionnaires to respondents to obtain data. The data analysis technique used in this study is multiple linear regression analysis. The results showed that the variables of service quality and price simultaneously had a positive and significant impact on customer satisfaction at Dalupa Trans. Service quality partially has a positive and significant influence on customer satisfaction. Price partially does not have a positive and significant impact on customer satisfaction at Dalupa Trans. The limitations of this study are that researchers only examine the variables that affect customer satisfaction, namely service quality and price. Suggestions For future researchers, they can re-examine the variables of this study with other types of transportation service businesses. In addition, further research can add other variables which are factors that influence customer satisfaction. Keywords: Customer satisfaction, Service Quality, Price